Dynamics of Exchange Rate Fluctuations in Turkey: Evidence from Symmetric and Asymmetric Causality Analysis - Çeli̇k, Ali (Ekonomika, 2022)
This study examines the factors affecting exchange rate fluctuations in Turkey by employing the quarterly data from 2008 to 2020. In this context, linear and nonlinear unit root tests were used to determine the stationarity levels of the variables. Then, symmetric and asymmetric causality analysis was preferred to ascertain the relationship between the variables. Symmetric causality analysis results indicated a causality relationship from the exchange rate to the long-term debt stock, from the credit default swap (CDS) to the exchange rate, and from the exchange rate to the uncertainty index. The asymmetric causality analysis showed a causality relationship from positive shocks in the short-term debt stock to negative shocks in the exchange rate. Also, it was proven that there exists a causality relationship from negative shocks in the short-term external debt stock to positive and negative shocks in the exchange rate. Another result demonstrated a causality relationship between positive shocks in the exchange rate to negative shocks in the long-term debt stock. In addition, it was found that negative shocks in net capital investment were the cause of negative shocks in the exchange rate, while it was determined that there was a causality relationship from positive shocks in the net reserves to positive shocks in the exchange rate. In conclusion, the asymmetric causality relationship from positive shocks in CDS to positive shocks in exchange rates was detected.
Keywords: Exchange Rate; Non-Linear Unit Root Test; Symmetric Causality Analysis; Asymmetric Causality Analysis